Isolation and Identification Bacteria Pseudomonas aeruginosa from adelt patients infected of otitis media and Curing of some Antibiotic Resistance and found content of G+C% - Intesar abduljabar shamkhe; Abdul Kareem Fattah Omar (Tikrit Journal of Pure Science, 2023)
Sixteen isolate of  Pseudomonas aeruginosa were collected from patients infected of otitis mediafor adelt people and diagnosed by biochemical teset and API20E these isolate tested for their resistance to Ampicillin,  Amoxillin, Chloramphenicol,  Trimethoprime, Tetracyclin, Cephotaxim, Amikacin, Gentamycin, Rifampicin and ciproflaxin. For the removal of the resistance  against the antibiotics in our isolates plasmid curing experiment was performed by using physical agent (elevated temperature). The results indicated that high temperature (47°C) was efficient to cure all the plasmids, and some isolates became sensitive to antibiotics. The extraction of chromosomal DNA was done to estimate the mol% of G+C of  DNA content to all  isolates the results the results showed that it was a taxonomic importance and it was at range (66.1- 67.3%).